Gestão do conhecimento e repositórios institucionais nas instituições de ensino e pesquisa na Região Norte do Brasil - Oliveira, Edson de Sousa (2019)
Institutional repositories of open access to scientific information (IRs) have emerged with the purpose of managing and providing greater visibility to the scientific production of universities and research institutions. One of the challenges of the operation of IRs is the understanding of the process of management of scientific communication within educational and research institutions, permeated by the management of scientific knowledge. In this context, this research aims to understand the process of management of scientific communication in the scope of Education and Research Institutions of the Northern Region of Brazil. From the methodological point of view, it is a study of a qualitative and descriptive purpose. The research universe consisted of actors that make up the scientific communication system, mainly the IRs of educational and research institutions. The sample was intentional non-probabilistic, based on criteria that are specific for each group of actors. The method adopted was the survey by means of a questionnaire, analysis of validators RCAAP and survey of the site of the IRs of the region. The data were collected through a research instrument with open and closed questions, identifying the category or group of actors and then submitted to textual analysis. Among the results of the research, it was possible to produce a current diagnosis of the situation of IRs in the northern region. In this way, the analysis revealed the strengths and challenges among the experiences described. The analysis revealed the reality of two of the most important instruments for the promotion of open access: the creation of IRs in the region that can be explained by the IBICT and the initiative of information professionals through the Charter of Belém until the creation of the North Network of Institutional Repositories - North RIAA created an environment for the creation and implementation of IRs, and another issue is the information and functioning policies of IRs for access openness and visibility of the academic production of the Institutions as a resource for planning the next steps of open access and collaborative networks in the North.